Peluang dan tantangan perkembangan green sukuk di Indonesia - Luthfia Ayu Karina (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
Along with the incessant issue of environment-based development and sustainable development, the funding requested to fund reforestation projects continues to increase. The principles of investment in Islamic finance synergize with the concept of environmentally friendly and sustainable development. The presence of Islamic financing instrument innovations based on sustainable development such as Green Sukuk in Indonesia has become a potential and important to support economic development in harmony with environmental conservation efforts. Despite getting a positive response from the market, there are many opportunities for the development of Green Sukuk in Indonesia that can be maximized as well as challenges in practice that can be minimized. This research will focus on Green Sukuk discussions, developments, opportunities and challenges in Indonesia.